Ovarian Follicular Dynamics, and Hormonal and Biochemical Profile in Post-Pubertal and Postpartum Jaffrabadi Buffaloes - Raval, Rupesh J; Parmar, Kiran H; Dhami, Arjun J; Kavani, Fulabhai S (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
Jaffrabadi buffalo is one of the heaviest buffalo breeds of the world (800 kg) and is known for poor reproductive efficiency. There is ascarcity of normal physiological data regarding reproductive parameters of Jaffrabadi buffalo. The primary objective of this study wasto elucidate ovarian follicular dynamics, hormonal and biochemical profiles in 10 post-pubertal heifers (n=5 each of age 42±2 and 48±2months) and five >90 days postpartum lactating buffaloes. Ultrasound monitoring of ovaries of animals was done at weekly interval and all follicles with diameter 8 mm (large follicles) as well as CLs identified were recorded. Blood samples were also collected soon after each USG from all animals for assay of hormonal and biochemical profiles. The findings revealed that the average number of small, medium and large follicles, total number of follicles per ovary as well as diameters of largest and subordinate follicles varied greatly among periods between three groups. The size of corpus luteum ranged from 13.7 to 21.2 mm, 13.7 to 23.9 mm and 15.3 to 22.7 mm, respectively, in Group-I, II and III. In the first week of study, significantly higher (p
Keywords: : Biochemical profile; Hormonal profile; Jaffrabadi buffalo; Ovarian follicular dynamics; Post-pubertal heifers